Assessment of health seeking behaviour among fishermen community in Puducherry - Neethiselvan, Rajarajeswari; S., Gayathri; P., Shanmughapriya (International Journal Of Community Medicine And Public Health, 2021)
Background: Fishermen community are involved in dangerous and complex profession and have diverse and untold constrains like work overtime in sea- nightshifts and late- night return from sea which worsen their morbid conditions. Objectives were to explore the health seeking behaviour and challenges faced by the fishermen community to utilize the health care facility in Puducherry. Methods: A community based cross-sectional study was conducted among 102 individuals in the selected villages of fishermen community in Puducherry based on convenient sampling during September 2019 to November 2019. Results: Majority 63 (62.4%) utilized government hospitals for various illness. Nearly one-third of people 35 (34.5%) visited private hospital for their ailments and another 4 (3.9%) preferred pharmacies for their illness. More than half of the study participants working as an active fisherman 59 (57.8%) had approached health care facility during their illness (p<0.037). Around 54 (52.9%) subjects belonged to lower middle class visited health facility during their illness (p<0.046). Free of cost, 24×7 services, and easy accessibility, were reported as the commonest reason for choosing public health facility. Doctors availability, less time consumption and quality of medical care were the reasons for preferring private practitioners. Conclusions: Strengthening of public health care services near the fishermen community area is required to promote their health seeking behaviour. Also, special focus to be given for appropriate transport facility and arranging specialized healthcare professionals for this community.